2003
DOI: 10.1007/s005350300058
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pancreatitis in Japan: epidemiology, prognosis, diagnostic criteria, and future problems

Abstract: Chronic pancreatitis is a chronic clinical disorder characterized by irreversible damage to the pancreas and the development of histologic evidence of inflammation and fibrosis, and eventually the destruction and permanent loss of exocrine and endocrine tissue. A nationwide survey in Japan revealed an increase in the total number of patients treated for chronic pancreatitis from 32 000 in 1994 to 42 000 in 1999. The overall prevalence and the incidence rate of chronic pancreatitis also increased, from 28.5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 45 publications
2
62
2
6
Order By: Relevance
“…Our 15 patients filled criterion 1 (narrowing of the main pancreatic duct or enlargement of pancreas by imaging studies), together with criterion 2 (high serum ␥-globulin, IgG, or IgG4 or the presence of autoantibodies, such as anti-nuclear antibodies and rheumatoid factor) and/or criterion 3 (marked interlobular fibrosis and prominent infiltration of lymphocytes and plasma cells in the periductal area). Serum samples were taken from 25 patients with chronic alcoholic pancreatitis, who were diagnosed according to a history of alcohol abuse, impaired exocrine pancreatic function, and the presence of calcified precipitates in the pancreas by imaging studies [Japan Pancreas Society, criteria for chronic pancreatitis 2001 (12)]. Twenty-five serum samples were recruited from patients with pancreas tumor (cancer [n ϭ 8] and intraductal papillary mucinous tumor [IPMT, n ϭ 17]).…”
Section: Methodsmentioning
confidence: 99%
“…Our 15 patients filled criterion 1 (narrowing of the main pancreatic duct or enlargement of pancreas by imaging studies), together with criterion 2 (high serum ␥-globulin, IgG, or IgG4 or the presence of autoantibodies, such as anti-nuclear antibodies and rheumatoid factor) and/or criterion 3 (marked interlobular fibrosis and prominent infiltration of lymphocytes and plasma cells in the periductal area). Serum samples were taken from 25 patients with chronic alcoholic pancreatitis, who were diagnosed according to a history of alcohol abuse, impaired exocrine pancreatic function, and the presence of calcified precipitates in the pancreas by imaging studies [Japan Pancreas Society, criteria for chronic pancreatitis 2001 (12)]. Twenty-five serum samples were recruited from patients with pancreas tumor (cancer [n ϭ 8] and intraductal papillary mucinous tumor [IPMT, n ϭ 17]).…”
Section: Methodsmentioning
confidence: 99%
“…The results of the latter study regarding the etiology of chronic pancreatitis were subsequently confirmed by others in Europe [10][11][12][13][14][15][16][17] as well as in Brazil [18] , Australia [19] and South Africa [20] . On the other hand, four consecutive surveys carried out in Japan (from 1970 to 1977, from 1978 to 1984, in 1994, and in 1999, respectively) [21] showed that alcohol as an etiological factor accounted for fewer than 60% of chronic pancreatitis cases in this country. The study by Sarles et al [9] reported that India is the most characteristic country in which patients with chronic pancreatitis were mainly malnourished in childhood, had a low fat and low protein diet and were not alcoholics.…”
Section: Introductionmentioning
confidence: 93%
“…One hundred nine patients with CP (63 males and 46 females; age range, 25-81 years; mean, 56.8 years) who fulfilled clinical diagnostic criteria for CP by the Japan Pancreas Society [12] and 116 healthy controls (69 males and 47 females; age range, 26-93 years; mean, 56.5 years) were selected for this study. Patients and healthy controls with recent inflammatory diseases, e.g.…”
Section: Patientsmentioning
confidence: 99%
“…CP patients were classified according to a staging system reported previously (Table 1) [12][13][14] . The staging system comprises 6 parameters: exocrine pancreatic function (scored 0-3), pancreatic imaging tests by endoscopic retrograde cholangiopancreatography (ERCP; scored 0-4), glucose metabolism (scored 0-4), pain (scored 0-4), alcohol intake (scored 0-2), and complications associated with CP (scored 0-2).…”
Section: Patientsmentioning
confidence: 99%